The effect of changes in surface winds and ocean stratification on coastal upwelling and sea surface temperatures in the Pliocene. (18th April 2017) - Miller, Madeline D.; Tziperman, Eli
Abstract: Sea surface temperature (SST) in subtropical eastern boundary upwelling zones is shown to be affected by three main factors: large‐scale ocean stratification, upwelling‐favorable sea surface wind stress, and the surface concentration (baroclinicity) of the alongshore pressure gradient driving the incoming geostrophic flow which balances the Ekman surface outflow. Pliocene‐aged SST proxies suggest that some combination of differences in upwelling forcing enable the sea surface temperatures in these zones to increase by up to 11°C. We find that large warming in SST in response to the three factors, of up to about 10°C in addition to a mean Pliocene ocean warming of 2–3°C, is concentrated in the direct upwelling zone. In the location of proxy sea surface temperatures, about 120 km away from the coast, and outside the coastal upwelling zone, the SST response to changes in wind and stratification is weaker, only accounting for up to 3.4°C above the mean Pliocene warming. Increased baroclinicity of the alongshore pressure gradient has a smaller effect, accounting for less than 2°C increases at both the coast and proxy site. The SST seaward (westward) of the upwelling zone is primarily determined by ocean‐atmosphere heat exchange and basin‐scale ocean forcing, rather than by changes in upwelling. The spatial pattern of SST change with each of the three forcing factors is similar, and therefore, all could contribute to the Pliocene‐modern difference in coastal SST. Key Points: This is the first study of mid‐latitude Pliocene upwelling site warmth using a model that resolves the narrow upwelling front dynamics Effects of wind stress and ocean stratification, and of a newly proposed role for alongshore baroclinic pressure gradient, are quantified Even for dramatic changes in upwelling forcings, warming at proxy sites, >100 km from coast, is 3.4°, compared with 8° suggested by proxies